The Morphological Structure of Verbs in Surah Al-Alaq - Afiya salih Aemarah Almadani (Journal of Scientific and Human Dimensions, 2025)
This research aims to study the 'morpheme' and to compare this study with the term 'word' used by the ancients, showing that what the early scholars addressed in their study of the concept of 'word' contained clear references to the idea of the morpheme. Accordingly, the study specifically addresses its concept, clarifies its types and categories, as it has become one of the main pillars in the structure of linguistic units in the modern era. They even made it the most important analytical unit in modern morphological studies, not only in Arabic but in various languages. At the end of the research, we provided a practical example from the Holy Quran and analyzed it based on the theoretical material we presented.
Keywords: Structural; Punctuation; Verbs